(3GdbeQ GdefjQ aj YbhO cJGH GdJMQjQs - (3LeGd GdOjf Ydj Hf GdMSjf Hf jMji Hf jMjis; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s ((3Ydi Hf SdGeI Hf jMji GdUQjei s)
(3ChdgG (B:s
(3cJGH GdfcGM (B_ (3HGH PcQ GdfSGA GddhGJi jMQe fcGMgf s
(3BNQgG (B:s
(3BNQg ef CKfGA cJGH GdHjY (B: (3hcPdc dh Yde Mjf ETJQGgG CfgG eZVhHI aGSJhdOgG , bVi ddeZUhH HgG hHChdGOgG EfbVi GdLRA GdKGfi ef cJGH GdbeQ GdefjQ s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis